Māori in Australia and the 2011 Election and Referendum - Bargh, Maria (Kicking the tyres : the New Zealand general election and electoral referendum of 2011, 2012)
Keywords: Elections – New Zealand; New Zealand – Politics and government – 21st century; New Zealand Parliament – Elections; 2011; Political parties – New Zealand; Proportional representation – New Zealand; Referendum – New Zealand; Representative government and representation – New Zealand

The Fragmentation of Māori Politics - Godfery, Morgan (Kicking the tyres : the New Zealand general election and electoral referendum of 2011, 2012)
Keywords: Elections – New Zealand; New Zealand – Politics and government – 21st century; New Zealand Parliament – Elections; 2011; Political parties – New Zealand; Proportional representation – New Zealand; Referendum – New Zealand; Representative government and representation – New Zealand

The Māori Party - Smith, Kaapua (Kicking the tyres : the New Zealand general election and electoral referendum of 2011, 2012)
Keywords: Elections – New Zealand; New Zealand – Politics and government – 21st century; New Zealand Parliament – Elections; 2011; Political parties – New Zealand; Proportional representation – New Zealand; Referendum – New Zealand; Representative government and representation – New Zealand

Mana - Minto, John; Potter, Helen; Sykes, Annette (Kicking the tyres : the New Zealand general election and electoral referendum of 2011, 2012)
Keywords: Elections – New Zealand; New Zealand – Politics and government – 21st century; New Zealand Parliament – Elections; 2011; Political parties – New Zealand; Proportional representation – New Zealand; Referendum – New Zealand; Representative government and representation – New Zealand

Chapter Thirteen: New Māori Politics 1990s-2000s - Bargh, Maria (Huia histories of Māori: ngā Tāhuhu Kōrero, 2012)
"Collection of 17 essays from Māori scholars which cover customary law, ancestral law, the natural world, Māori urban protest, health, politics, and customary language and expression"–Publisher's information.
Keywords: elections; government relations; history; iwi; iwi chairs forum; kāwanatanga; mana party; māori electorates; māori seats; social conditions; te pāti māori; tikanga | indigenous law; tāngata whenua; voting

Māori Urban Protest Movements - Taonui, Rawiri (Huia histories of Māori: ngā Tāhuhu Kōrero, 2012)
"Collection of 17 essays from Māori scholars which cover customary law, ancestral law, the natural world, Māori urban protest, health, politics, and customary language and expression"–Publisher's information.
Keywords: discrimination; foreshore and seabed act 2004; government relations; hikoi ki waitangi; history; kaitiakitanga; land march; māori womens welfare league; nga tamatoa; parihaka; poverty; protest; racism; rangatiratanga; resistance; social conditions; springbok tour protests; takaparawhau bastion point; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi; tāngata whenua; urbanisation

Chapter Seventeen: 'As for these blankets, burn them' Māori and Indigeneity - Hokowhitu, Brendan (Huia histories of Māori: ngā Tāhuhu Kōrero, 2012)
"Collection of 17 essays from Māori scholars which cover customary law, ancestral law, the natural world, Māori urban protest, health, politics, and customary language and expression"–Publisher's information.
Keywords: government relations; history; identity; indigenous rights; pan-indigenous movement; social conditions; tikanga | indigenous law; tāngata whenua

Rights and Sovereignty of Indigenous Peoples: Implications for Foreign Policy - Bargh, Maria (Public Participation in Foreign Policy, 2012)
The predominant forms of foreign policy discussed these days are underpinned by an assumption of Crown sovereignty in Aotearoa New Zealand. However, the first diplomatic relations and foreign policy in this country were conducted by hapū and iwi Māori.1 Prior to the 1800s, Māori had a long history of interaction in the Pacific and with other nations. Such interactions were governed by specific legal and political practices and institutions. A number of the concepts upon which these practices and institutions were based included whakapapa (genealogy), utu (balance), mana (respect) and koha (reciprocity).2
Keywords: diplomacy; foreign policy; free trade agreement; hapū politics; human rights; international relations; iwi politics; te ao Māori

"Assaulting the Ears of Government": The Indian Homemakers' Clubs and the Maori Women's Welfare League in Their Formative Years - Harris, Aroha (Indigenous Women and Work: From Labor to Activism, 2012)
Keywords: history; mana wāhine; native americans